Tree regeneration potential in urban spruce-dominated forests is shaped by management history - Korhonen, Aku; Vuorilampi, Heli; Katavisto, Oskar; Immonen, Auli; Hamberg, Leena
With projected climate change, urban spruce-dominated forests are facing increasing risks of forest damages, encouraging management for mixed stand structures. In the major cities of southern Finland, forests are preferentially maintained continuously covered, and tree regeneration is mostly reliant on naturally emerging sapling stock. To understand the role of forest management in shaping natural tree regeneration in urban forests, we studied the occurrence and abundance of tree saplings in spruce-dominated tree stands on a management continuum ranging from partially logged to undisturbed near-natural stands. Study sites (N = 74) were located in three urban centers in southern Finland: Tampere, Lahti and Helsinki region. We analyzed the data by comparing tree regeneration potential between management classes reflecting the timing and intensity of past logging, and by relating the occurrence of saplings with current structures of the living tree stand. Compared to undisturbed stands, partially logged sites had increased regeneration of broad-leaved trees and repressed regeneration of spruce, while the most abundant sapling tree species across all management classes was rowan. We conclude that partial logging can be a successful way of directing tree regeneration towards lower dominance of spruce. However, when the canopy is only partially opened, created gaps may end up being filled primarily by rowans that are comparatively shade-tolerant. Because the ingrowth of rowan and many other broad-leaved tree species is strongly restricted by dense populations of large browsing animals in non-urban areas, urban forests may develop stand structures and tree species composition that are otherwise rare in the Fennoscandian boreal forests. 2023